Potensi Asap Cair Tempurung Kelapa Sebagai Antijamur Fusarium Foetens, Fusarium Moniliforme, Dan Colletotrichum Capsici - Purwantisari, Susiana; Sari, Dyah Maharani Sisya Puspita; Risnanda, Meizulfa Ayu; Khanifah, Neni Nur; Amatullah, Lutfiana Hary; Mahardhika, Wahyu Aji (Jurnal Penelitian Hasil Hutan, 2023)
Fusarium and Colletotrichum are pathogenic fungi that attack potato and chili plants. Farmers often use synthetic fungicides to control the disease, while the continuous use of synthetic fungicides can cause negative impact to environment. This study aimed to test the effectiveness of plant disease control by using coconut shell liquid smoke. Inluded rejuvenation of isolates, characterization of tested isolates, and liquid smoke antifungal tests using the well diffusion method, and data analysis. Five formula concentrations were applied namely 0% (negative control), 10%, 20%, and 30% concentration, and antracol as positive control. The measurement of inhibition (mm) was carried out after 7 days of incubation. The result of in vitro effectiveness test showed that the liquid smoke had the ability to inhibit the growth of pathogenic fungi Fusarium foetens, F. moniliforme, and Colletotrichum capsici with the best concentration of 30%.